Feedback controller and observer design to maximize stability radius - Akmeliawati, Rini; Chee, Pin Tan (2006)
In this paper we provide a robust feedback controller and observer design to provide a maximum stability radius. The technique would take into account the performance specifications in the design process. This is done by using the Linear Matrix Inequalities (LMI). The technique is illustrated on a feedback controller and observer design of an inverted pendulum.